The economic costs of conserving genetic resources at the CGIAR centres - Koo, Bonwoo; Pardey, Philip G.; Wright, Brian D. (Wiley, 2003)
The 11 genebanks of the Consultative Group on International Agriculture (CGIAR) have grown considerably in size over the past few decades, currently holding about 666,000 accessions of germplasm. Conserving germplasm is a very long run, if not in perpetuity, proposition. The mismatch between the mainly annual funding support for this conservation effort and its very long‐term nature and intent is a serious concern. Using the results of five CGIAR genebank case studies (accounting for 87% of the total CGIAR genebank holdings), we estimate the size of an endowment or trust fund that would be required to assure a funding stream to conserve this genetic material for future generations. The annual cost (in year 2000 US$) of conserving and distributing the genetic material presently held in all 11 CGIAR genebanks is estimated to be 5.7 million US$ (mUS$), which could be maintained for all future generations by setting aside a fund of 149 mUS$ (invested at a real rate of interest of 4% per annum). This would be sufficient to underwrite the costs for the CGIAR's current conservation activities in perpetuity (estimated to be 61 mUS$), as well as the cost of maintaining the distribution activities (88 mUS$) that provide germplasm to breeders, scientists, farmers and others world wide.